Wideband reconfigurable entire Ku‐band metasurface beam‐steerable reflector for satellite communications - David Rotshild; Amir Abramovich (IET Microwaves, Antennas & Propagation, 2019)
A novel reconfigurable metasurface beam‐steerable reflector for satellite communication which covers the entire Ku‐band, and supports 300 MHz bandwidth, is suggested in this work. The reflector is based on a new type of electromagnetic bandgap. Varactor diodes are used to change each unit cell capacitance of the metasurface reflector allowing phase spatial control of the reflected beam. This approach is known in the literature and is presented in many sub 6 GHz reflector studies and very few in X‐band. For higher frequencies such as Ku‐band, the size of the unit cell should be reduced. Thus, the dimensions of the varactor diode are no longer negligible relative to the metasurface unit cell dimensions, causing significant absorbance and scattering. Elimination of that absorbance and scattering can be achieved if the varactor diode is located on the back side of the suggested reflector, without deviating from the lumped element model approximation, thus enabling low‐cost voltage‐controlled reflector surface for Ku‐band. Manufacturing considerations for the new suggested wide dynamic stirring range Ku‐band reflector are given. Furthermore, the simulation results show wide bandwidth support and good performances for normal and off‐normal incident radiation to the reflector surface.